Simple, Reproducible, and Efficient Clinical Grading System for Murine Models of Acute Graft-versus-Host Disease - Naserian, Sina; Leclerc, Mathieu; Thiolat, Allan; Pilon, Caroline; Le Bret, Cindy; Belkacemi, Yazid; Maury, Sébastien; Charlotte, Frédéric; Cohen, José L. (Frontiers in Immunology, 2018)
Acute graft-versus-host disease (aGVHD) represents a challenging complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Despite the intensive pre-clinical research in the field of prevention and treatment of aGVHD, and the presence of a well-established clinical grading system to evaluate human aGVHD, such a valid tool is still lacking for the evaluation of murine aGVHD. Indeed, several scoring systems have been reported, but none of them has been properly evaluated and they all share some limitations: they incompletely reflect the disease, rely on severity stages that are distinguished by subjective assessment of clinical criteria and are not easy to discriminate, which could render evaluation more time-consuming, and their reproducibility among different experimenters is uncertain. Consequently, clinical murine aGVHD description is often based merely on animal weight loss and mortality. Here, we propose a simple scoring system of aGVHD relying on the binary (yes or no) evaluation of 5 important visual parameters that reflect the complexity of the disease without the need to sacrifice the mice. We show that this scoring system is consistent with the gold standard histological staging of aGVHD across several donor/recipient mice combinations. This system is also a strong predictor of survival of recipient mice when used early after transplant, and is highly reproducible between experimenters.